2017
DOI: 10.1016/j.jhealeco.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of e-cigarette indoor vaping restrictions on adult prenatal smoking and birth outcomes

Abstract: We estimate the effect of county-level e-cigarette indoor vaping restrictions on adult prenatal smoking and birth outcomes using United States birth record data for 7 million pregnant women living in places already comprehensively banning the indoor use of traditional cigarettes. We use both cross-sectional and panel data to estimate our difference-in-difference models. Our panel model results suggest that adoption of a comprehensive indoor vaping restriction increased prenatal smoking by 2.0 percentage points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 20 publications
(29 reference statements)
2
21
0
Order By: Relevance
“…Hence, the net effect of ENDS MLSAs on birth outcomes is ambiguous and requires empirical investigation. ENDS indoor vaping restrictions were found to have no effect on birth outcomes for adult pregnant women, potentially because these effects cancelled each other out (Cooper & Pesko, 2017…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the net effect of ENDS MLSAs on birth outcomes is ambiguous and requires empirical investigation. ENDS indoor vaping restrictions were found to have no effect on birth outcomes for adult pregnant women, potentially because these effects cancelled each other out (Cooper & Pesko, 2017…”
Section: Methodsmentioning
confidence: 99%
“…information from the American Non-Smokers Rights Foundation, which we used to calculate the percent of the population covered by bans on vaping in private workplaces, bars, and restaurants (Cooper & Pesko, 2017).…”
Section: Datamentioning
confidence: 99%
“…In addition, theory predicts that smoking bans would have inhibitory effects on tobacco consumption. In addition, smoking ban requires smokers to make additional investments of time to smoke at nonregulated places (Chaloupka & Warner, 2000;Cooper & Pesko, 2017). Smoking restrictions also can change individual's smoking behavior by increasing vdisutility from consuming tobacco products because of changes in social norms regarding the acceptability of smoking (Jones et al, 2015).…”
Section: Previous Researchmentioning
confidence: 99%
“…Adda and Cornaglia (2010) showed that U.S. state-level smoking ban on workplaces, restaurants, and bars did not affect the proportion of people who smoked or attempt to quit but led smokers to spend more time at home smoking. Cooper and Pesko (2017) also found that U.S. county-level electronic cigarette indoor vaping restrictions led to an increase in consumption of traditional tobacco products among pregnant women. Cooper and Pesko (2017) also found that U.S. county-level electronic cigarette indoor vaping restrictions led to an increase in consumption of traditional tobacco products among pregnant women.…”
mentioning
confidence: 94%
See 1 more Smart Citation